Current biologics in treatment of pemphigus foliaceus: a systematic review - Carver, Caden A.; Kalesinskas, Mikole; Ahmed, A. Razzaque (Frontiers in Immunology, 2023)
Background: Pemphigus foliaceus (PF) differs from pemphigus vulgaris (PV) in that it affects only the skin and mucous membranes are not involved. Pemphigus is commonly treated with systemic corticosteroids and immunosuppressive agents (ISAs). More recently, biologics have been used. The current literature on biologic therapy often combines treatment of PF with PV, hence it is often difficult for clinicians to isolate the treatment of PF from PV. The purpose of this review was to provide information regarding the use of current biological therapy, specifically in PF. Materials and Methods: A search of PubMed, Embase, and other databases was conducted using keywords pemphigus foliaceus (PF), rituximab (RTX), intravenous immunoglobulin (IVIg), and biologics. Forty-one studies were included in this review, which produced 105 patients with PF, treated with RTX, IVIg, or a combination of both. Eighty-five patients were treated with RTX, eight patients with IVIg, and 12 received both RTX and IVIg. Results: Most patients in this review had PF that was nonresponsive to conventional immunosuppressive therapies (CIST), and had significant side effects from their use. RTX treatment resulted in complete remission (CR) in 63.2%, a relapse rate of 39.5%, an infection rate of 19.7%, and a mortality rate of 3.9%. Relapse was greater in the lymphoma (LP) protocol than the rheumatoid arthritis (RA) protocol (p<0.0001). IVIg led to CR in 62.5% of patients, with no relapses or infections. Patients receiving both biologics experienced better outcomes when RTX was first administered, then followed by IVIg. Follow-up durations for patients receiving RTX, IVIg, and both were 22.1, 24.8, and 35.7 months, respectively. Discussion: In pemphigus foliaceus patients nonresponsive to conventional immunosuppressive therapy or in those with significant side effects from CIST, RTX and IVIg appear to be useful agents. Profile of clinical response, as well as relapse, infection, and mortality rates in PF patients treated with RTX were similar to those observed in PV patients. The data suggests that protocols specific for PF may produce better outcomes, less adverse effects, and improved quality of life.